PERBANDINGAN KUALITAS AIR BERDASARKAN KADAR COLIFORM PADA DEPOT AIR MINUM ISI ULANG YANG DI MASAK DAN YANG TIDAK DI MASAK DI KECAMATAN PADANG GELUGUR KABUPATEN PASAMAN TAHUN 2024 - Novela, Vina; Susanty, Shantrya Dhelly (Universitas Fort De Kock, 2025)
Refill Drinking Water Depot (DAMIU) is a business providing bulk drinking water without packaging that is in demand by the public because the price is cheaper than bottled water. However, its quality is still in doubt due to the lack of information about the processing and supervision process. This study aims to compare water quality based on coliform levels in boiled and uncooked DAMIU water in Padang Gelugur District, Pasaman Regency. The study was conducted quantitatively with a laboratory experimental design in February - March 2025, involving 6 depots with a total sampling technique. Data were obtained through laboratory tests and analyzed univariately and bivariately. The results showed an average coliform level in boiled water of 527 CFU / 100 mL, and uncooked water of 523.67 CFU / 100 mL. The highest level was in depot C (597 CFU / 100 mL) and the lowest in depot A (77 CFU / 100 mL). The results of the independent samples t-test obtained Pvalue = 0.990 ≥ α (0.05) (Ho is accepted). This means that there is no difference in water quality based on the coliform levels of the refill drinking water depots, cooked and uncooked. It is concluded that there is no difference in coliform levels between cooked and uncooked DAMIU water. It is recommended that DAMIU managers in Padang Gelugur District improve hygiene and sanitation during the water treatment process to meet quality standards and be free from coliform contamination